NASOLABIAL CYST: A CASE REPORT OF A RARE NON-ODONTOGENIC SWELLING WITH EMPHASIS ON RADIOLOGICAL DIFFERENTIATION - Dr Prajwala N,; Dr Sachin Shetty,; Dr G Murugan, (IJRDO-Journal of Applied Science, 2025)
Nasolabial cysts are uncommon, non-odontogenic soft-tissue cysts located in the nasolabial fold. They represent a small fraction of maxillofacial cysts, typically presenting as a painless swelling, sometimes associated with nasal obstruction. This report details the case of a 37-year-old male who presented with a slowly enlarging right nasolabial swelling over three years, accompanied by mild pain and nasal blockage. Clinical and computed tomography (CT) imaging revealed a well-defined soft tissue lesion measuring approximately 2.9×2.7 cm, demonstrating scalloping of the adjacent maxilla. The cyst was completely excised via a sublabial approach, and histopathological analysis confirmed the diagnosis of a nasolabial cyst. The patient experienced an uneventful recovery with no recurrence observed at two-month follow-up. This case underscores the importance of considering nasolabial cysts in the differential diagnosis of facial swellings and highlights complete surgical excision as the definitive treatment, offering an excellent prognosis.